A review of the efficacy of popular eye cream ingredients - Hanin Hamie, BS; Reem Yassine, BS; Rajaa Shoukfeh, BS; Dilara Turk, MD; Farhan Huq, MD; Meena Moossavi, MD, MPH (Wolters Kluwer, 2024)
Background:. Due to the periorbital region's high susceptibility to damage from external factors, along with its tendency to demonstrate early signs of aging, periorbital skin is a common target for antiaging therapy. Objective:. This review aims to evaluate the efficacy of active ingredients commonly found in eye creams, particularly focusing on their impact on periorbital skin concerns. Methods:. A comprehensive review of the literature on active ingredients in eye creams, including retinoids, vitamins C and E, peptides, ceramides, hyaluronic acid, caffeine, and niacinamide, was conducted. Clinical studies assessing the efficacy of these ingredients in addressing periorbital concerns were examined. Results:. Studies demonstrate the potential of these ingredients to improve various aspects of periorbital skin, including hydration, elasticity, collagen synthesis, and reduction of inflammatory mediators. Ingredients such as retinoids, vitamin C, and caffeine show promise in addressing wrinkles and hyperpigmentation, while peptides and hyaluronic acid aid in collagen production and hydration. Niacinamide and ceramides offer benefits in reducing wrinkles and enhancing the skin barrier function. Limitations:. The lack of clinical trials specifically targeting eye cream formulations and periorbital skin is a notable limitation. Furthermore, the variability in study designs, sample sizes, and concentrations of active ingredients across studies complicates direct comparisons. Conclusion:. The reviewed studies highlight the potential of active ingredients in eye creams to address various periorbital concerns. Further research, particularly large-scale clinical trials focusing on eye cream formulations and their efficacy on periorbital skin, is warranted to establish their significance and comparability with other dermatologic products.